Penatalaksanaan Latihan Isometrik dan Pemberian Diet Rendah Purin dengan Masalah Keperawatan Nyeri Akut pada Pasien Gout di Desa Joho - Ivanarose Ari Rakasiswi; Deden Dermawan Deden (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Gout or gout is an inflammation of the joints caused by high levels of uric acid in the body (hypersemia), resulting in accumulation of deposits of monosodium urate crystals that collect in the joints, this occurs because the body has impaired purine metabolism. One of the nursing problems that often arise in gout sufferers is acute pain. One of the recommended non-pharmacological therapies is joint mobility exercise therapy, namely isometric exercises. The novelty of this research is to add the act of giving a low purine diet as a complementary measure to treat the pain experienced by gout patients. The aim of this study was to describe the management of isometric exercise and administration of a low-purine diet with acute pain nursing problems in gout patients. Method: The method used in research uses qualitative methods with a case study approach. The technique for taking research subjects is non-probability sampling with a purposive sampling approach. The research subjects were 3 gout sufferers. Result: The results obtained from the data of the three subjects experienced a decrease in pain on a scale of 6, pain in the knees and heels. The results of the physical examination of the research subjects obtained the results: good general condition, composmentis awareness, TTV: TD; 160/100 mm Hg, RR; 20 x/min, N; 86 x/min, S; 36.8 0C, facial expression with pain, limited range of leg movements, no abnormalities of the feet and hands, no tremors, no walking aids. The nursing diagnosis is acute pain related to biological agents of injury (high purine levels). Researchers implemented isometric exercises 3 times in 1 week and administered a low purine diet to gout patients for 1 week. The evaluation showed reduced pain data after isometric exercise and given a low-purine diet. Conclusion: isometric exercise and administration of a low purine diet in gout patients to reduce pain.